Effect of biomimetic material on stress distribution in mandibular molars restored with inlays: a three-dimensional finite element analysis - Zhu,Junxin; Luo,Danmei; Rong,Qiguo; Wang,Xiaoyan (PeerJ, 2019)
Background Although biomimetic material has become increasingly popular in dental cosmetology nowadays, it remains unclear how it would affect the restored teeth during chewing. It is necessary to study the influence of biomimetic material on stress distribution in the restored teeth. Methods Eight three-dimensional finite element (FE) models were constructed and divided into two groups. Group 1 included the FE model of intact molar, and the FE models of inlay-restored molars fabricated from IPS e.max CAD, Lava Ultimate and biomimetic materials individually. Enamel was considered a homogeneous material. Group 2 included the FE models of intact molar and molars restored with inlays using IPS e.max CAD, Lava Ultimate and biomimetic materials individually, considering enamel as an inhomogeneous material. Results In Group 1, compared with that in the intact molar, the maximum tensile stress (MTS) in the occlusal grooves decreased in the inlay-restored molars fabricated from IPS e.max CAD and was concentrated on the cavity floor at the buccal side in the inner dentin around inlay. When Lava Ultimate was selected, MTS decreased in the occlusal grooves and on the cavity floor but increased in the lateral walls. In the restored molar using biomimetic material, the MTS on the cavity floor was distributed more evenly than that in the molar using IPS e.max CAD, and no obvious changes were noted in the lateral walls. The same changes were observed in Group 2. No differences in the stress distribution pattern were noted among the FE models in Groups 1 and 2. Conclusions Molars restored with inlays fabricated from biomimetic material exhibit a more uniform stress distribution in the dentin around restoration. The consideration of enamel as a homogeneous tissue is acceptable for analyzing the maximum principal stress distribution in the inlay-restored molar.
Keywords: Finite element analysis; Biomimetic Materials; Enamel; Inhomogeneous nature